Management of Safety for Quality Construction - Husin, Husrul Nizam; Adnan, Hamimah; Jusoff, Kamaruzaman (2008)
An overview of construction quality and safety reveals many striking similarities for these two management concept. Programs that have been developed to improve quality and safety performance have many elements in common. In some cases safety is considered a part of Total Quality Management (TQM). The close relationship between quality and safety implies that benefits would be derived by applying some or all of the following propositions: (1) Consolidate the safety and quality functions; (2) Apply quality concept to safety; (3) Optimize the safety management concept; and (4) Apply the results of safety aspects to quality. Within these past few years, the Malaysian government has made an effort on executing safety and health policies through the enforcement of guidelines as well as conducting site safety seminars and certifications. Ranked as a second industry in Malaysia that contribute to highest percentage of accidents at the worksite, the impact of loss of profit and unhealthy workplace affect the construction industry. Currently, these topics are being widely implied and stressed out in Malaysia by the means of enforcement; for instance, through ISO certification and local regulations and guidelines. This paper aim to provide a basis framework, this seminar which titled “Safety Management towards Quality Construction” tries to delineate the relationship and the importance of these two areas. The concepts of safety management and quality management indeed are still new in Malaysia. A proposed model which is also a framework is seen as a procurable method on defining the basic concept of safety management meant to achieve the expected quality level. In the aspect of proposing safety application model, a directive method of the Total Quality Management is used. A basic management application model as suggested by Walker (1993), is proposed to be used as a generic model to highlight the key features. Findings from individual survey are used to delineate the key points or processes of the safety application model.